Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam melalui Strategi Inferencing - Tetin, Tetin; Herlina, N. Hani; Tantowie, Tanto Aljauharie (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2021)
This research is motivated by the level of completeness of the learning outcomes of class III students of MI Rijalul Hikam Jatinagara, Jatinagara District, Ciamis Regency, which is still low in the SKI subject. The average student learning outcomes in the SKI subject obtained by students are still below the minimum completeness criteria of 75. However, the reality shows that 30% of 17 students have not reached the KKM while 70% of 17 students have reached the KKM. This is because the learning process is more teacher-centered and monotonous. Learning activities are mostly used to take notes so that students become bored. This situation makes students less understanding of the material being taught and easy to forget so that it affects the low student learning outcomes. The research method used was Classroom Action Research (CAR) with Kurt Lewin's model. The sequence of activities in Kurt Lewin's model is planning, acting, observing and reflecting. The data collection techniques used in this research were test, observation, interview and descriptive analysis techniques. Data analysis data selection, data correction and data weighting. After conducting the research, the following data can be obtained: 1) the ability of the teacher in preparing RPP SKI in the first cycle reaches an average of 82.61 (Good); in cycle II reached 86.5 (Good); and in the third cycle reached an average of 93.14 (Very good), 2) the ability of teachers to carry out the learning process of the IEC learning process in the first cycle reached an average of 79.02 (good); in cycle II reached an average value of 86.5 (good); and in cycle III reached an average value of 93.33 (very good). 3) student learning outcomes in the first cycle reached 83.05 (good) with 70.5% completeness in the calculation of 12 students completed, 5 students have not completed. In cycle II it reaches an average of 88.23 (good) with completeness 88.23% on the calculation of 15 students complete, 2 students have not completed and in cycle III reaches an average value of 92.88 (good) with 100% completeness in the calculation all students (22 students) completed. This proves that the Inferencing strategy (concluding) can improve student learning outcomes.